Representation of Class and Class Relationships in Iranian Cinema Case Study of “a Separation: Nader and Simin” - Mohammad Rezaei; Arash Hasan pour; Simin Daneshgar (Taḥqīqāt-i Farhangī-i Īrān)
During recent decades, many social and economic transformations that occurred in Iran behind ongoing changes in the formation, relations and identity of Iran current classes. One of the text in which these categories are represented is “A separation”. In this article we examined class and class relationship, in this film (text) by taking representation approach and semiotics method.Analyzing film codes shows that in this film, two classes are represented: The middle class and the lower class. The middle class through identity aspect is modern and disposed to West but unsettled and disjointed. The lower class also represented as Underprivileged Class that having religious approach to life and is in tradition life-world. Also, film, represent new class formation of Iran societyand relation interim.  In fact, filmin addition represents this duality, narrate the separation and deep and sweep social gap in different levels of Iranian society that constantly reproduced by class member with differentiation of self from others and show ideological and antagonistic aspect of class relationship.